Strengthening of Biomolecular Engineering Competence for Pharmacists in Batu City through Webinars and Workshops on Isolation of Genetic Material, Real-Time PCR, and its Applications in the Clinical Field - Rehmadanta Sitepu; Godeliva Adriani Hendra; F.X. Haryanto Susanto; Aditya Nirwana (Journal of Community Practice and Social Welfare, 2022)
The pandemic of COVID-19 has forced pharmacist assistance practitioners to strive to improve their qualifications and competencies, especially in molecular biology. The human resources competencies in this field are still lacking, resulting in some obstacles in the handling of COVID-19 encountering, thus hampering the acceleration of post-pandemic recovery. The Virus that can spread rapidly requires competent health workers to move as quickly as possible to overcome this pandemic condition. Ignorance of these critical technical matters often occurs so that it affects the identification results, which are expected to be more accurate, precise, and reliable. In a workforce to increase the competency capacity of pharmacist assistants in the biomolecular field, especially in the technical competence of genetic material isolation and PCR methods, the Pharmacy Study Program of Ma Chung University held Webinars and Workshops related to DNA isolation and quality testing. The webinar and workshop on the isolation of genetic material were carried out to implement one of the research topics in the Pharmacy Study Program, especially in the field of development of molecular biology. The essential thing in this webinar and workshop is discussing some critical criteria before the actual virus identification. This program collaborates with PAFI (Indonesian Pharmacy Experts Association) of Batu City as a partner. People who took part in this event consisted of 63 persons from the Batu City and Malang City areas. Most of the participants work in health facilities, with 50% of the participants having isolated genetic material and PCR (Polymerase Chain Reaction). Spreading the pre and post-test with the same questions increased the average acknowledgment score from 42.9 to 61.1. This indicates that continuous training in this field needs to be held on an ongoing program so that the competence of pharmacists in the field of molecular biology is getting better.